TOTAL POPULATION GROWTH IN PALANKA’S TOWN NOVYI KODAK ON THE EVE OF NOVA SICH DESTROYING (BASED ON CONFESSION LISTS) (Південний архів (історичні науки), 2024)
The purpose of the article is to analyze total population growth and its components (natural increase, migration coefficient) and other indicators influenced on it like: natality, nuptuality, marriage structure, population age and sex structure. The main method used in the article is data modeling. Model is based on: 1. Extrapolation of Cossack’s stratum total population growth on whole population group in the town. 2. Extrapolation of birth rates from previous periods (extracted from the population age and sex structure by component method) on the father years. Model includes the assumption that natality did not changed in time and mortality level was not high. That is why birth rates were equal natural increase in the model. Cohort analysis was used for analyzing other indicators. Research results demonstrate that Novyi Kodak total population on the moment of Zaporizhzhian Sich destroying in 1775 year could be estimate from 2916 to 4577 persons by the model data. The percent of “hidden” from taxation population was near 57 %. Natural increase was higher than migration increase. The level of the first one was near 45 % and the second one – near 33 %. Common people had the highest birth rates (41 %) and highest total birth rate (7.6), meanwhile Cossacks had highest marital indexes (13 %). Marriages with medium age lag (6–10 years) were most popular. The natality dynamic for previous periods (before 1764) demonstrates decrease in 1739, 1745, and 1759–1760 years. The last decrease (1759–1760) was the most noticeably among Cossacks. Author makes the conclusion that model data correspondence with previous estimates of total population in Novyi Kodak. This fact can verify model faithfulness. The population of the town was growing mainly through birth rates and not the migration flow. Nevertheless, influence of the last one was high. There can be made hypothesis that single women (probably young widows) were one of the parts of migrants. They could made a competition in the marriage market, because of what not all of women during the period of the first and second widowhood could find a pair. This led to marriages with a large age difference. Population age and sex structure in the town was normal and belonged to the progressive type, but inhabitants, first – Cossacks, suffered significant losses in the male population through Russian-Turkish war 1735–1739 years. Migrants arrived to the town were previously from common people, while the Cossack population consisted of local residents (lived in the city at least since the 1730s). Further researches can be connected with prosopography and case studies of some migrants to Novyi Kodak at the same period. Another direction of research can be connected with comparative studies of demographic indicators between various settlements on the territory of Zaporizhzhian Sich and Cossack Hetmanate.
Keywords: natality, nuptuality, age and sex population structure, Zaporizhzhian Sich, Cossacks, eighteenth century.